Lost Identity: Analyzing The Psychological Struggles of Marco in The Movie "The Childe" (2023) - yanti, cita; sari, intan (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This study explores the psychological struggles and identity crisis of Marco, the main character in The Childe (2023). It aims to identify the psychological factors contributing to Marco’s identity conflict and examine how these struggles influence his character development throughout the film. By describing phenomena and social conditions as well as the content analysis in the movie, the study analyzes key scenes, dialogues, and symbols reflecting Marco’s inner turmoil. The findings reveal that Marco’s loss of identity is rooted in repressed trauma, emotional instability, and a breakdown in the balance between the id, ego, and superego. His fragmented memory, impulsive behavior, and denial of his familial identity reflect classic Freudian defense mechanisms. Analyzing the Psychological Struggles, such as repression and displacement. These symptoms demonstrate a fractured ego struggling to mediate between unconscious desires and social reality. Furthermore, Marco’s identity confusion aligns with Erikson’s psychosocial stage of identity vs. role confusion, wherein unresolved trauma prevents a coherent self-concept. The film portrays his psychological journey not as a linear recovery, but as a cyclical confrontation with suppressed truths. Through cinematic expressions—such as physical violence, symbolic imagery, and emotional breakdowns— the film illustrates how trauma shapes identity and behavior. This research highlights the relevance of psychoanalytic theory in analyzing cinematic narratives and offers interdisciplinary insights into trauma, masculinity, and psychological resilience. Keywords: Identity crisis, Marco, Psychoanalytic theory, Repressed trauma, Sigmund Freud, The Childe (2023)